Norms And Interrelationships Of Quality Attributes Of Fresh, Refrigerated And Cryopreserved Buffalo Semen - Chaudhari, D. V.; Dhami, A. J.; Patel, A. C. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
This study was undertaken on semen ejaculates (n=48) of six mature Surti buffalo bulls. Following evaluation the ejaculates were extended in standard TFYG (Tris-citric acid-fructose-egg yolk glycerol) diluent at 34°C temperature keeping 100 x 106 sperm per ml. The fractions of extended semen samples were preserved at refrigeration preservation (5°C, 72 hrs) as well as at ultra low (-196°C) temperature using split sample technique. The semen filled in French mini straws was frozen in LN2 vapour using programmable biofreezer. The mean ± SE values of various spermatozoal attributes obtained of fresh, refrigerated and cryopreserved semen were within normal acceptable limit for the buffalo semen. The correlation matrix analysis was worked out for sperm motility, viability, normal morphology, intact acrosome and plasma membrane integrity in fresh semen, semen preserved at 5°C for 24 and 72 hrs and in post-thawed samples. There were significant (P<0.01) interrelationships (r = 0.29 to 0.94) observed between sperm motility, viability, 5normal morphology, intact acrosome and plasma membrane integrity in fresh, refrigerated and cryopreserved buffalo semen, which proved that initial motility and membrane integrity can be used as predicative measures of cryopreservability of buffalo semen in routine evaluation.